Biosynthesis of silver nanoparticles through tandem hydrolysis of silver sulfate and cellulose under hydrothermal conditions. Issue 12 (3rd December 2013) - Li, Xianxue; Odoom‐Wubah, Tareque; Chen, Huimei; Jing, Xiaolian; Zheng, Bingyun; Huang, Jiale
Abstract BACKGROUND Biosynthesis of Ag nanoparticles (AgNPs) utilizing renewable materials and nontoxic chemicals has become highly desirable and is currently receiving tremendous attention. In this study, a facile and cellulose‐based approach was developed to biosynthesize AgNPs through tandem hydrolysis of silver sulfate and cellulose under hydrothermal conditions. RESULTS Well‐defined AgNPs of about 72.0 nm in size were biosynthesized with 0.30 g of cellulose at 200°C for 10 h. The particle sizes of the as‐synthesized AgNPs were positively affected by the reaction temperature and time, but on the contrary were negatively affected by the amount of cellulose employed. The results from Fourier transform infrared spectroscopy showed that the cellulose‐hydrolyzed products (saccharides or aldehydes) were accountable for the bioreduction of the Ag ions, and the C = O (C–O) groups in the aldehydes or saccharides played critical roles in capping the AgNPs. Additionally, in the presence of the as‐synthesized AgNPs, enhanced surface fluorescence of methyl orange was achieved. CONCLUSION A biological and maneuverable strategy was successfully developed for the synthesis of AgNPs by a hydrothermal route through tandem hydrolysis of silver sulfate and cellulose. Thus, this environmentally friendly method is anticipated to be utilized for the biosynthesis of AgNPs and opens up avenues to prepare other metal nanoparticles from metal sulfates. © 2013 Society of Chemical Industry